2019
DOI: 10.1007/s00223-019-00586-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Use of Androgen Deprivation Therapy (ADT) in Men with Prostate Cancer Increase the Risk of Sarcopenia?

Abstract: Androgen deprivation therapy (ADT) for prostate cancer (PCa) can compromise muscle health. Hence, we aimed to quantify the prevalence of sarcopenia (i.e., compromised lean mass, muscle strength, and physical function) in ADT-treated (> 12 week) men (n = 70) compared to similarly aged non-ADT-treated PCa (n = 52) and healthy controls (n = 70). Lean and fat mass were quantified by dual-energy X-ray absorptiometry. Muscle strength and function were measured using handgrip dynamometry and gait speed, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
11
1
1
Order By: Relevance
“…There have been growing interests in muscle health and sarcopenia in those with prostate cancer. Although previous studies have reported the adverse effect of androgen deprivation therapy on muscle mass and quality in patients with prostate cancer, 26,27 hormone therapy did not affect the presence of sarcopenia in our study. This was probably due to the clinical heterogeneity of the patients who had received hormone therapy.…”
Section: Discussioncontrasting
confidence: 92%
“…There have been growing interests in muscle health and sarcopenia in those with prostate cancer. Although previous studies have reported the adverse effect of androgen deprivation therapy on muscle mass and quality in patients with prostate cancer, 26,27 hormone therapy did not affect the presence of sarcopenia in our study. This was probably due to the clinical heterogeneity of the patients who had received hormone therapy.…”
Section: Discussioncontrasting
confidence: 92%
“…The increased risk of fractures following androgen-inhibition is due to increased osteoclastic bone destruction in addition to muscle dysfunction and increased risk of fall [ 4 ]. Reduced testosterone has a negative impact on muscle mass, which may lead to less mobility, further contributing to decreased BMD [ 24 , 25 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decline in skeletal muscle mass and function is a common problem in older cancer patients which can negatively affect physical function and cancer outcomes (Handforth et al, 2014;Owen et al, 2019;Williams et al, 2020). The significant difference between mean grip strength declined as a result of increasing age, when compared with normative data, 70% of the scores for men <65 years were below age-matched norms, compared to 53% in the >75 years group.…”
Section: Discussionmentioning
confidence: 99%